MICROBIAL ENRICHMENT PROCESS IN THE ANODE OF MICROBIAL FUEL CELL SYSTEM USING TOFU WASTEWATER (TWW) ANAEROBIC SLUDGE - Satar, Ibdal; Permadi, Adi; Latifatunnajib, Sukma (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2021)
Microbial fuel cell consisting two main components which are anode and cathode materials. In the microbial fuel cell, both anode and cathode compartments are separated with a separator. Anode generates the protons and electrons while cathode converts protons into water with the presence electrons and oxygen. During the Microbial fuel cell operation, the performance of anode is very crucial due to it provides the protons and electrons. Hence, the high efficiency microbial fuel cell is very related with the high anode performance. This work addressed to the enrichment process of electroactive bacteria (EAB) in anode of microbial fuel cell. In this work, some parameters such as current generations, , and pH changes were used to assess the enrichment process of EAB was reached. In addition, the presence of EAB on the anode surface was identified based on the morphology of anode surface. The removal of COD and the pH value were determined by using the American public health analysis method and pH tester, respectively. The morphology of anode surface was analysed by using a scanning electron microscope. Whereas, current generation was tested by using a mustimeter. The removal of COD and final pH were obtained 71.4 % and 5.7, respectively. The optimum current generation was observed 0.19 mA. The surface morphology of anode before enriched with microbes was clear surface, while after enriched with microbes was attached by microbes. The removal of COD, pH changes, current generation and morphology of anode surface could be used to assess the EAB in the anode compartment.      Keywords: Microbial fuel cell; anode; cathode; electroactive bacteria; pH changes.